Non-aggregating zinc phthalocyanine sensitizer with bulky diphenylphenoxy donor groups and pyrazole-3-carboxylic acid anchoring group for coadsorbent-free dye-sensitized solar cells - Yildiz, Burak; Arslan, Baris Seckin; Guzel, Emre; Nebioglu, Mehmet; Menges, Nurettin; Sisman, Ilkay; Sener, M. Kasim (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
A novel unsymmetrical zinc phthalocyanine complex (PCA-ZnPc-3) containing six 2,6-diphenylphenoxy donor groups and pyrazole-3-carboxylic acid anchoring group has been synthesized and used as a sensitizer for dye sensitized solar cells (DSSCs). The optical, electrochemical and photovoltaic characteristics were evaluated and compared with the dyes containing the same anchoring group and tert-butyl (PCA-ZnPc-1) or hexylsulfanyl (PCA-ZnPc-2) donor groups, developed by our group. The DSSC with PCA-ZnPc-3 exhibited a higher power conversion efficiency (PCE) of 2.04% as compared to that of PCA-ZnPc-1 (PCE = 1.74%) and PCA-ZnPc-2 (PCE = 1.89%). This enhancement in efficiency may be ascribed to the less dye aggregation and appropriate dye coverage. These results suggest that the incorporation of 2,6-diphenylphenoxy into pyrazole-3-carboxylic acid based zinc phthalocyanine sensitizers can improve photovoltaic performance of DSSCs.
Keywords: Dye-sensitized solar cell; Phthalocyanine; Pyrazole-3-carboxylic acid; 2,6-Diphenylphenoxy donor group; ORGANIC-DYES; PERFORMANCE; EFFICIENCY; Energy & Fuels